2021
DOI: 10.3390/gels7040195
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Chemical Properties of Geopolymer Gels Incorporated with Neodymium and Samarium

Abstract: The present work was focused on doping of 1% and 5% both of Nd2O3 and Sm2O3 in geopolymer gels. One of the main goals was to determine the influence of the behavior of Nd and Sm as dopants and structural nanoparticles changes of the final geopolymer formed. It is shown that the disorder formed by alkali activation of metakaolin can accommodate the rare earth cations Nd3+ and Sm3+ into their aluminosilicate framework structure. The main geopolymerization product identified in gels is Al-rich (Na)-AS-H gel compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The presence of the Nd 4d spectral line in the low-energy scale of the spectrum is a consequence of the amount of Nd concentration. Previous investigations showed that, at a lower dopant concentration, the Nd 4d line does not appear [ 37 ]. Detailed spectra od neodymium 3d and 4d spectral lines reveal the more pronounced contribution of Nd 3d 5/2-1 to 998.9 eV belonging to Nd (OH) 3 , as well as its contribution to 977.9 eV (Nd 3d 5/2-2), and can be attributed to pure Nd 2 O 3 , as shown in Figure 7 c. The ratio of the amounts of hydroxide and oxide phase offers information about the reaction rate of neodymium in the geopolymer matrix during alkaline activation.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the Nd 4d spectral line in the low-energy scale of the spectrum is a consequence of the amount of Nd concentration. Previous investigations showed that, at a lower dopant concentration, the Nd 4d line does not appear [ 37 ]. Detailed spectra od neodymium 3d and 4d spectral lines reveal the more pronounced contribution of Nd 3d 5/2-1 to 998.9 eV belonging to Nd (OH) 3 , as well as its contribution to 977.9 eV (Nd 3d 5/2-2), and can be attributed to pure Nd 2 O 3 , as shown in Figure 7 c. The ratio of the amounts of hydroxide and oxide phase offers information about the reaction rate of neodymium in the geopolymer matrix during alkaline activation.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the presence of zeolite A in the formulations of geopolymers based on Brazilian metakaolins [ 14 ], the consolidated geopolymers displayed high adsorption capacity within short times (between one and five minutes) for different cationic dyes, i.e., methylene blue, safranin, and malachite green from aqueous solutions. From the observation of such an encapsulating capability, the number of studies dedicated to different cations [ 15 , 16 , 17 , 18 , 19 ], anions [ 20 , 21 ], and larger molecular assemblages [ 22 ] has increased over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers, also called geopolymer gels (Nenadović et al, 2021), are materials made from alumino-silicate materials, such as metakaolin (MEFISTO L05, 2022), furnace slag (Trinh et al, 2020) fly ash (Kristály et al, 2020) or precursors prepared synthetically via sol-gel method (Tsai et al, 2010), which are primarily composed of silicon dioxide, aluminium oxide, iron oxide and other oxides. They are formed by polycondensation in strongly basic environment, usually in hydroxide or silicate solution.…”
Section: Introductionmentioning
confidence: 99%